Optimal design of hydrofoil and marine propeller using micro-genetic algorithm (Î¼GA) - Karim, Md Mashud; Suzuki, K; Kai, H (Journal of Naval Architecture and Marine Engineering, 2009)
This paper presents results from the application of the genetic algorithm (GA) technique to the design optimization of hydrofoil and marine propeller incorporating potential based boundary element method (BEM). Although, larger population size as implemented by simple genetic algorithm (SGA) could find the optimal individual after a fewer number of generations than smaller population size, it is penalized by a longer amount of time to evaluate fitness in every generation. An investigation is, therefore, conducted in this research to implement micro genetic algorithm (Î¼GA) with a very small population, and with simple genetic parameters, in order to achieve faster convergence to better solution from generation to generation. The technique is applied here to optimize hydrofoils of different plan forms, e.g., rectangular, elliptical, trapezoidal etc. Firstly, the hydrofoil design parameters, such as, angle of incidence, maximum thickness and camber ratios, aspect ratio, taper ratio, angle of sweep etc. are initialized randomly and the generated hydrofoil is analyzed by potential based boundary element method. GA then updates the design parameters over generation after generation and finally, finds an improved hydrofoil of maximum lift-drag ratio or minimum drag coefficient satisfying some design constraints. An improved blade or hydrofoil section is also designed by GA satisfying some design constraints. Finally, the technique is applied to the optimum design of marine propeller. In this study, Î¼GA is found useful and prospective tool for the design optimization of hydrofoil and marine propeller due to its faster convergence. Keywords: Genetic algorithm, boundary element method, hydrofoil, propeller, design optimization Â doi: 10.3329/jname.v1i1.2038 Journal of Naval Architecture and Marine Engineering 1(2004) 47-61